PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP ALOKASI BELANJA DAERAH - Purpitasari, Puput; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of Local Own Source Revenue and General Allocation Fund to the Local Government Budget Allocation on the District or City Government in East Java. The population is 38 districtsand cities government in East Java. The sample observation was in 2009 â 2013 periods and thepopulation is 76 items.The results of the research show that i.e.: 1) the Local Own Source Revenue has positive and significant influence to the local budget in which the LocalOwn Source Revenuesconsist of tax, retribution, local own enterprises and other legal Local Own Source Revenuesare the important income source for a region in fulfilling their expenses. 2) the general allocation fund has positive and significant influence to the local government budget in which the general allocation fund is the important income source for a region in fulfilling their expenses as well as to show the independent level of a region. 3) The Local Own Source Revenue which was started in 2009-2013 had experienced animprovement in East Java, therefore East Java province could fulfill the development in each region without depends on the funds which were sourced from the central government which was the general allocation fund.Keywords: Local own source Revenue, General Allocation Fund, Local Government Budget